Cost analysis of potentially inappropriate medication in older hospitalized patients. (1st November 2020) - Pagès, Arnaud; Mazon, Marine; Cool, Charlène; McCambridge, Cécile; Cestac, Philippe; Rouch, Laure; Juillard-Condat, Blandine
ABSTRACT: Objectives : Pubmed literature search show that the prescription of potentially inappropriate medications is a major concern in older hospitalized patients, both from a clinical and financial perspective. This study aims to identify factors associated with exposure and potentially inappropriate medication costs in older hospitalized patients and to assess the financial impact of substituting these medications with safer alternatives. Methods : We performed an observational cross-sectional study of all patients aged 75 years or older hospitalized in a university hospital (except geriatric wards) on a given day. Potentially inappropriate medications were identified using European and French guidelines. Results : A total of 365 patients were included. At least one potentially inappropriate medication was prescribed in 50.4% of these patients. This contributed 19.7% [16.1; 23.6] to the average cost of medication per patient. Substitution of these medications with recommended alternatives was cost saving: average incremental cost per patient: −3.97 € [−7.21; −1.58]. Both polypharmacy and type of ward providing care were associated with increased costs of potentially inappropriate medications. Conclusions : This study assessed the prevalence of potentially inappropriate medications in older hospitalized patients and established that their substitution by alternative medications provided a cost saving.